1993
DOI: 10.1016/0741-5214(93)90162-f
|View full text |Cite
|
Sign up to set email alerts
|

Splenic infarction after splenorenal arterial bypass

Abstract: Because of the spleen's extensive collateral circulation, the risk of splenic infarction after splenorenal arterial bypass (SRB) has been considered negligible. We report four patients in whom splenic infarctions developed after SRB. Splenic infarction developed in one patient at the time of SKB, and symptoms of splenic abscess (fever, abdominal pain, and leukocytosis) that proved to be splenic infarctions at laparotomy developed in three patients 2 to 16 days after the operation. Factors possibly contributing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
5
0

Year Published

2000
2000
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 12 publications
0
5
0
Order By: Relevance
“…10 The potential complication of splenic infarction may be prevented by ligation of the artery proximally away from the splenic hilum. 11 Compared with the technique of diversion of superior mesenteric venous flow by mesocaval shunt with downstream ligation of the superior mesenteric vein, 12 splenic artery ligation is a technically simpler procedure that easily can be added to a complicated transplant operation.…”
Section: Discussionmentioning
confidence: 99%
“…10 The potential complication of splenic infarction may be prevented by ligation of the artery proximally away from the splenic hilum. 11 Compared with the technique of diversion of superior mesenteric venous flow by mesocaval shunt with downstream ligation of the superior mesenteric vein, 12 splenic artery ligation is a technically simpler procedure that easily can be added to a complicated transplant operation.…”
Section: Discussionmentioning
confidence: 99%
“…They suggested that the existing collateral circulation may not always sustain splenic viability. 6 The possibility of a steal phenomenon, resulting in either splenic or renal infarction, was of particular concern in our patient given that the spleen already was fully mobilized from its collateral circulation. To maximize the success of our revascularization, we elected to perform a splenectomy in this patient before constructing the anastomosis.…”
Section: Discussionmentioning
confidence: 84%
“…One of the most important aspects of our study is to draw attention to splenic abscesses or acute pancreatitis that may develop after SAT. Although splenic infarction following SpA ligation (4) or SpA interventions (5) has been described previously, the potential devastating consequences, such as splenic abscess, have been overlooked to date.…”
Section: Discussionmentioning
confidence: 99%